Structural and electronic impacts of the axialsSubstitution at the phosphorus center of C(sp3)-bridged P-heterotriangulenes - Harrer, Siegfried; Schühle, Johannes D. R.; Neiß, Christian; Günthert, Marina; Mittmann, Lena; Reule, Andrea; Leitner, Jonas; Rominger, Frank; Görling, Andreas; Kivala, Milan (European journal of organic chemistry, 2024)
The structural and electronic properties of the dimethylmethylene-bridged P-heterotriangulene have been systematically modulated by functionalization of its phosphorus center. The optoelectronic properties of the obtained derivatives in solution were characterized by UV/Vis absorption and emission spectroscopy, cyclic voltammetry and 31P NMR spectroscopy. The solid state structures were analyzed by X-ray crystallography. The experimental results were corroborated by density functional theory calculations which revealed the crucial influence of the axial substitution on the bowl-shaped geometry of the phosphorus-centered polycyclic scaffold, which is proportional to the s-character of the P−X bond. The advantage of the bowl-shaped P-heterotriangulene scaffold was demonstrated by successful co-crystallization with fullerene C60.
Gesehen am 11.10.2024